Initial experience of restorative proctocolectomy for ulcerative colitis by transanal total mesorectal rectal excision and single‐incision abdominal laparoscopic surgery. (December 2016) - Leo, C. A.; Samaranayake, S.; Perry‐Woodford, Z. L.; Vitone, L.; Faiz, O.; Hodgkinson, J. D.; Shaikh, I.; Warusavitarne, J.
Abstract: Aim: Laparoscopic surgery is well established for colon cancer, with defined benefits. Use of laparoscopy for the performance of restorative proctocolectomy (RPC) with ileoanal anastomosis is more controversial. Technical aspects include difficult dissection of the distal rectum and a potentially increased risk of anastomotic leakage through multiple firings of the stapler. In an attempt to overcome these difficulties we have used the technique of transanal rectal excision to perform the proctectomy. This paper describes the technique, which is combined with an abdominal approach using a single‐incision platform (SIP). Method: Data were collected prospectively for consecutive operations between May 2013 and October 2015, including all cases of restorative proctocolectomy with ileoanal pouch anastomosis performed laparoscopically. Only patients having a transanal total mesorectal excision (TaTME) assisted by SIP were included. The indication for RPC was ulcerative colitis (UC) refractory to medical treatment. Results: The procedure was performed on 16 patients with a median age of 46 (26–70) years. The male:female ratio was 5:3 and the median hospital stay was 6 (3–20) days. The median operation time was 247 (185–470) min and the overall conversion rate to open surgery was 18.7%. The 30‐day surgical complication rate was 37.5% (Clavien–Dindo 1 in four patients, 2 in one patient and 3 in one patient). One patient developed anastomotic leakage 2 weeks postoperatively. Conclusion: This initial study has demonstrated the feasibility and safety of TaTME combined with SIP when performing RPC with ileal pouch–anal anastomosis for UC.